Employer's rights and contractor's liabilities in relation to construction defects after final certificate [electronic resource] - 230256 Tan, Pei Ling (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2007